2018
DOI: 10.1111/mmi.14141
|View full text |Cite
|
Sign up to set email alerts
|

Two pKM101‐encoded proteins, the pilus‐tip protein TraC and Pep, assemble on the Escherichia coli cell surface as adhesins required for efficient conjugative DNA transfer

Abstract: Summary Mobile genetic elements (MGEs) encode type IV secretion systems (T4SSs) known as conjugation machines for their transmission between bacterial cells. Conjugation machines are composed of an envelope-spanning translocation channel, and those functioning in Gram-negative species additionally elaborate an extracellular pilus to initiate donor-recipient cell contacts. We report that pKM101, a self-transmissible MGE functioning in the Enterobacteriaceae, has evolved a second target cell attachment mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 104 publications
3
20
1
Order By: Relevance
“…Deletion of the pep gene from pKM101 led to a 10 2 -fold decrease in conjugative transfer frequency, and similar decreases were observed for the four point mutants of pep, each of which possessed the substitution at one of the four conserved Cys residues (27). Our detailed analysis of various mpfK mutants of NAH7 in this study exhibited the following properties: 10 2 -to 10 3 -fold reduced transferability of the four Cys-to-Ala single-substitution mutants and two double-substitution mutants (MpfK C39A-C88A and MpfK C44A-C54A ) and no transferability of the four other double-substitution mutants or a quadruple-substitution mutant (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Deletion of the pep gene from pKM101 led to a 10 2 -fold decrease in conjugative transfer frequency, and similar decreases were observed for the four point mutants of pep, each of which possessed the substitution at one of the four conserved Cys residues (27). Our detailed analysis of various mpfK mutants of NAH7 in this study exhibited the following properties: 10 2 -to 10 3 -fold reduced transferability of the four Cys-to-Ala single-substitution mutants and two double-substitution mutants (MpfK C39A-C88A and MpfK C44A-C54A ) and no transferability of the four other double-substitution mutants or a quadruple-substitution mutant (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…S2) encode the MpfK homologs with high (76% to 100%) similarities to the MpfK protein. Although some non-IncP-9 conjugative plasmids encode the proteins with this superfamily domain, the experimentally analyzed proteins with the TrbM superfamily domain are limited to the pep product (44% amino-acid sequence similarity with MpfK) from an IncN plasmid pKM101 and the orf104 product (44% similarity) from another IncN plasmid, pCU101; both of these proteins are important for the efficient conjugative transfer (25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because T6SS firing is also induced by membrane-disrupting compounds such as polymyxin B, the authors concluded that the T6SS counterattack results from Mpf-mediated membrane disruption. Recent studies further showed that the production of two adhesins (TraC and Pep), or the formation of a T4SS channel, but not assembly of conjugative pilus, is capable of activating a T6SS counterattack (Gordon et al, 2017;González-Rivera et al, 2019). Therefore, T6SS firing could be a defensive weapon in response to various assaults challenging membrane integrity ( Figure 5).…”
Section: Recipient Signals Triggering the Type VI Secretion Systemmentioning
confidence: 99%